Association between Physicochemical parameter and The Presence of Escherichia Coli in Catfish - Hasna, Parakkasi (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Catfish may carry pathogenic bacteria that can cause harm when consumed. Therefore, this study is aimed to determine the level of physicochemical parameters in water and the distribution of Escherichia coli in water and catfish samples. In addition, the study was also done to determine the occurrence of pathogenic E. coli 0157:H7 in the samples. The study was done in one catfish farm and two wet markets. From each sampling site, 5 water and 5 catfish samples were collected. Therefore, a total of 45 samples composed of 15 catfish intestines, 15 catfish muscles and 15 water samples were used. Only water samples were subjected to physicochemical analysis while for microbial analysis, both water and catfish samples were analysed. Microbial analyses were done by using standard plate count followed by a series of biochemical tests and detection of E. coli 0157:H7 using multiplex PCR. The results showed that the selected physicochemical levels were in Class I as according to the National Water Quality Standards for Malaysia. The total heterotrophic bacterial count of water, catfish intestines and muscles ranged from 1.77 x 104 CFU/mL to 6.26 x 105 CFU/mL which both in the catfish muscle. From the 45 samples, E. coli spp. was present in all samples except in 3 catfish muscles where no E. coli spp. can be found. However, pathogenic E. coli 0 157:H7 was not det~ted in any of the samples. This indicates that the catfish and water samples are free from pathogenic E. coli 0157:H7.